Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Beth Brown, December 17, 1988 - Brown, Bethet al (1988)
Iowa Christmas bird counts of species found in Lucas contributed by Beth Brown, December 17, 1988. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1988-1989. Epson - sheet feed